2002
DOI: 10.1046/j.1365-4362.2002.01370.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐class 1 and class 2 antigens in Turkish patients with pemphigus

Abstract: We postulate that HLA-B35, B44, CW4, DR4, DR14, DQ4 and DQ8 antigens may be responsible for susceptibility to pemphigus while HLA-DR11, DQ7 and DQ2 antigens may have a protective role in the Turkish population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
3
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 10 publications
6
25
3
5
Order By: Relevance
“…The results of this study show that both class II and class I HLAs are related to the occurrence of pemphigus in southern Turkey. There are a few published reports on the distribution of HLAs in patients with pemphigus and in the healthy population in Turkey 14–17 . Kavala et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of this study show that both class II and class I HLAs are related to the occurrence of pemphigus in southern Turkey. There are a few published reports on the distribution of HLAs in patients with pemphigus and in the healthy population in Turkey 14–17 . Kavala et al.…”
Section: Discussionmentioning
confidence: 99%
“…HLA DRB1*04 allele has been found to be significantly increased in Ashkenazi Jewish patients, whereas the gene frequency of HLA DRB1*14 allele was reported to be significantly higher in pemphigus patients than in control subjects in European and American Caucasian groups, and Japanese and Mexican populations 7–11 . Although several studies on the genetic background of pemphigus have been published, only a few have reported the distribution of HLAs in Turkish populations with pemphigus 14–16 . These studies also have some limitations; HLA profiles were determined in small samples of patients, using insufficiently reliable methodology for HLA assessment or, occasionally, different techniques in the same study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies concern the Mediterranean Basin or Asia Minor (Bulgaria, Macedonia, Turkey, Israel, Iran, Tunisia and Greece) [1,2,4,5,6,7,8]. The crude incidence of auto-immune pemphigus in the world varies from 0.8 to 34/10 6 inhabitants [9,10,11,12,13]. Few studies have been performed with individual validation of the cases and calculation of the standardized incidence of the pemphigus.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that the disease is significantly associated with several HLA haplotypes 12–19 and that the family members of patients with autoimmune diseases are more susceptible to the development of the same or, more frequently, other autoimmune diseases 20 has hinted at a possible genetic component in the etiology of this disease. Moreover, environmental/exogenous factors seem to have a significant impact on the initiation/triggering of the autoimmune response and the disease expression; 21 for instance, traditional cosmetics (widely used by Tunisian women) are suspected to cause an excess of pemphigus cases among young women in rural Tunisia 22 …”
Section: Introductionmentioning
confidence: 99%